The Affective-Motivational Domain of the McGill Pain Questionnaire Discriminates Between Two Distinct Fibromyalgia Patient Subgroups – A Preliminary Study Based on Self-Organizing Maps - Salgueiro, Monika; Azkue, Jon Jatsu (IntechOpen, 2012)
None